2018
DOI: 10.1007/s10668-018-0095-1
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability performance evaluation of agricultural cooperatives’ operations: a systemic review of the literature

Abstract: The article proposes to construct and analyze the research landscape on the sustainability performance evaluation of agricultural cooperatives' operations. The research was characterized as a systematic review of the literature, carried out through the ProKnow-C structured process, complemented by a procedure known as Snowball to form the portfolio of articles, theses and dissertations to be studied. The research results highlight models for the evaluation of the sustainability of agricultural cooperatives' op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 27 publications
(33 reference statements)
2
33
0
3
Order By: Relevance
“…Cooperative organizations are emerging by having a philosophy that prioritizes collective rights over individual rights. Currently, cooperativeness can be found in several branches of economic activity, yet there is a great adhesion of cooperativeness in the agricultural sector [49]. From the point of view of time series Sustainability 2020, 12, 948 6 of 18 analysis, the work focuses on the period from 2005 to 2014, since a final and complete database of data was available for this period.…”
Section: Hypothesismentioning
confidence: 99%
“…Cooperative organizations are emerging by having a philosophy that prioritizes collective rights over individual rights. Currently, cooperativeness can be found in several branches of economic activity, yet there is a great adhesion of cooperativeness in the agricultural sector [49]. From the point of view of time series Sustainability 2020, 12, 948 6 of 18 analysis, the work focuses on the period from 2005 to 2014, since a final and complete database of data was available for this period.…”
Section: Hypothesismentioning
confidence: 99%
“…In their systemic review of the literature of the models of evaluation of the sustainability performance of agricultural cooperatives' operations, Marcis and colleagues identified that, as with performance indicators, most sustainability evaluation models for cooperatives do not address sustainability in an integrated way, with a predominance of economic and social aspects and a neglect for environmental dimensions (Matthews et al, 2016;Marcis et al, 2018). The quest for more efficient, cost effective and faster processes displace efforts on bigger questions such as those related to biodiversity, depletion of natural resources and power imbalances.…”
Section: Lock-in Cooperation Hindering Sustainable Practices: Industrmentioning
confidence: 99%
“…Phase 1 findings suggest that, despite the dominance of two business subcategories (i.e., BFA and BEA) in empirical co-op performance research, the Chapter 3 contributes to co-op literature by delivering a comprehensive dashboard for co-op performance assessment which mirrors the co-op organizational form idiosyncrasies and harmonizes business-social aspects. It supplements past systematic reviews on co-op performance (e.g., Marcis et al, 2018;Sexton and Iskow, 1993;Soboh et al, 2009;Van Herck, 2014) and advances the debate on how to best appraise it. Moreover, the interdisciplinary results of Actually, Chapter 3 helps co-ops to quantify their socio-economic impact consistently and, thereby, render their contribution to sustainable development more visible.…”
Section: Summary Of Major Findings Contributions and Implicationsmentioning
confidence: 71%
“…Third, the importance of agricultural co-ops has also been manifested by the marked attention they have received in academic literature (Höhler and Kühl, 2014). A significant advance of theoretical work has taken place in the last decades LeVay, 1983;Staatz, 1989;Valentinov and Iliopoulos, 2013), while studies on the performance of agricultural co-ops have enjoyed a long empirical tradition (Marcis et al, 2018;Soboh et al, 2009;Van Herck, 2014).…”
Section: Focus On Agricultural Co-opsmentioning
confidence: 99%
See 1 more Smart Citation